COVID-19 Announcements and Investor Reactions on the Australian Securities Exchange - Hadrian Geri Djajadikerta; Terri Trireksani; Kwadjo Appiagyei (Australasian Accounting, Business and Finance Journal, 2022)
The extraordinary situation due to COVID-19 pandemic has created an opportunity to examine the behavioural patterns of investors by way of the level of trading activities on the Australian Securities Exchange (ASX) around the releases of crucial information regarding the COVID-19 pandemic. This study aims to identify abnormal trading volume at ASX around eight selected significant announcements and measures of the COVID-19 pandemic in Australia. The study finds sufficient evidence to indicate that the COVID-19 announcements and calculations influence investor decisions on the ASX as the pandemic evolved.
Keywords: Investor reactions; COVID-19; Announcements; Australia; Australian Securities Exchange; ASX